Perancangan Konsep Museum Virtual Universitas Kristen Maranatha - Natanael, I Nyoman; Suhanjoyo, Shirly Nathania; Wianto, Elizabeth (Waca Cipta Ruang, 2023)
Maranatha Christian University Museum was officially established on October 16, 2015, to coincide with the 50th Anniversary of Maranatha Christian University. The museum, named "Museum Maranatha," presents a collection of historical objects related to the journey of Maranatha Christian University since its establishment in 1965. However, the Maranatha Museum still has obstacles in the form of limited visitor access, especially during the Covid-19 pandemic. On the other hand, information technology and media, proliferating at this time, can be used as a solution to the limited access of visitors to public spaces. The background of this research is an effort to present new virtual spaces so that access is not limited so that the purpose the importance of the historical aspects of the founding of Maranatha Christian University can be more widely known by the public, especially within the scope of Maranatha Christian University. The method used in this research is descriptive qualitative using purposive sampling and snowballing approach with relatively narrow inclusion criteria and is interested in the museum and its development. The collection and processing of data from respondents who were distributed exclusively to the Maranatha Christian University were considered when designing the virtual museum concept of Maranatha Christian University. Keywords: Maranatha Museum, Maranatha Christian University, Virtual Museum